Temperature Sensing in Agarose/Silk Fibroin Translucent Hydrogels: Preparation of an Environment for Long-Term Observation - Maria Micheva; Stanislav Baluschev; Katharina Landfester (Nanomaterials)
Environmental changes, such as applied medication, nutrient depletion, and accumulation of metabolic residues, affect cell culture activity. The combination of these factors reflects on the local temperature distribution and local oxygen concentration towards the cell culture scaffold. However, determining the temporal variation of local temperature, independent of local oxygen concentration changes in biological specimens, remains a significant technological challenge. The process of triplet–triplet annihilation upconversion (TTA-UC), performed in a nanoconfined environment with a continuous aqueous phase, appears to be a possible solution to these severe sensing problems. This process generates two optical signals (delayed emitter fluorescence (dF) and residual sensitizer phosphorescence (rPh)) in response to a single external stimulus (local temperature), allowing the application of the ratiometric-type sensing procedure. The ability to incorporate large amounts of sacrificial singlet oxygen scavenging materials, without altering the temperature sensitivity, allows long-term protection against photo-oxidative damage to the sensing moieties. Translucent agarose/silk fibroin hydrogels embedding non-ionic micellar systems containing energetically optimized annihilation couples simultaneously fulfill two critical functions: first, to serve as mechanical support (for further application as a cell culture scaffold); second, to allow tuning of the material response window to achieve a maximum temperature sensitivity better than 0.5 K for the physiologically important region around 36 °C.